Artkosmos-Fragmente. Stefan Holitschke. 2011 - Meidl, E (Polar Record, 2013)
Stefan Holitschke's slim volume adds to the vast amount of Arcticand Antarctic lyric responses to the extreme environments ofthe polar regions. Published by Asaro Verlag 2011 , its cover shows an icecarving of a polar bear whose head seems to have sufferedfrom melting. Arktokosmos is a curious edition which doesnot give any inforn:iation about the author: one must google hisbiographical details to find out that his 'lyrical fragments' werewritten as a result of wintering on Spitsbergen. According tohis own web site he is a 'dedicated IT specialist with additionalskills in circumpolar studies, law, economy and energy business'. Arktokosmos seems to be Holitschke's first foray into poetry.